Analisis Tingkat Efisiensi Pengelolaan Dana Zakat, Infak, Sedekah (ZIS) Melalui Pendekatan Data Envelopment Analysis (DEA) (Studi Kasus Pada BAZNAS Provinsi Sumatera Utara Priode 2016-2019) - Saragih, Lailan Usniyah; Imsar, Imsar; Syahbudi, Muhammad (Universitas Labuhanbatu, 2022)
Efficiency is a very important factor for the survival of a company or organization, both macro and micro and only focuses on the National Amil Zakat Agency (BASNAZ) of North Sumatra province and this study was only conducted from December 2020 to July 2021. This study aims to determine the level of efficiency BAZNAS North Sumatra province so that BAZNAS can evaluate, minimize errors and determine policies that will be done to improve the performance of BAZNAS seen from the input and output variables. This study uses a type of quantitative research using BAZNAS financial statements obtained from the official website sumut.baznas.go.id observation period 2016-2019. The method used in this study is the ratio approach and non-parametic Data Envelopement Analysis (DEA) with intermediation approach. The results of this study as a whole has reached the level of 100% efficiency in the period 2016-2019 through the DEA method with an intermediation approach. While in the ratio approach the level of efficiency is far from efficient.